Spatial and temporal variability of biomass and composition of green tides in Ireland - Bermejo-Lacida, Ricardo; Heesch, Svenja; Mac Monagail, Michéal; O´Donnell, Moya; Daly, Eve; Wilkes, Robert J.; Morrison, Liam (Elsevier, 2019)
The identification of relevant scales of variation is a necessary prerequisite before explanatory models can be proposed and tested. In this study spatial and temporal patterns of biomass distribution were assessed for two Ulva morphologies in two Irish estuaries heavily affected by green tides (wet biomass>1 kg m−2 during the peak bloom). Moreover, using genetic markers, the species composition of these green tides was assessed. Results revealed that these blooms were multi-specific, with Ulva prolifera, U. compressa and U.rigida the most frequent species. The species U. prolifera and U. compressa usually showed a tubular morphology, while U. rigida was mainly laminar. A seasonal succession common to both estuaries was also identified, with the bloom dominated by tubular species during spring and early summer, and co-dominated by tubular and laminar morphologies during late summer and autumn. Moreover, tubular and laminar morphologies exhibited different distribution patterns, with tubular morphologies varying at bigger spatial scales and higher biomass than the laminar. As tubular and laminar morphologies exhibited different distribution patterns, varying tubular morphologies along bigger spatial scales with higher biomass levels than the laminar. Considering that tubular morphologies were usually anchored to the sediment, while laminar Ulva were usually observed free-floating, these differences could explain a differential influence by water motion. An important annual and decadal variability in biomass levels of Ulva was observed, in the case of the Tolka estuary a noticeable increase over the last two decades. These findings should be considered for the development of management and monitoring strategies since the different habitat of laminar and tubular morphologies (anchored vs. free-floating) may play an important role in the balance of nutrients and biomass in the estuary, or determine the response to pollutant exposure.
Artículo científico sobre mareas de macroalgas en Irlanda
Keywords: Biodiversidad; Ulva; Green tide; Macrogal bloom; Eutrophication; Temporal succession; Biodiversity